Communication Barriers in Comprehending GKII Mission Month Preaching in 2022 - SISWANTO , Krido; NOVEL, Elisjul Chaiska; KOTE, Ivony Eunike Putri; PANGKALI, Olivia (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
There is a scarcity of literature available that examines the emergence of indigenous Christian ministry in post-independence Indonesia. As a result, the impact of Christian missions needs to be evaluated objectively and comprehensively. The Indonesian Bible Tent Church had chosen "Put out into the deep" as the theme for Mission Month in 2022. However, the subject was explored in local churches for four weeks, with many subthemes. According to preliminary research findings, some church members appeared to have difficulty grasping the theme. As a result, this study was carried out to determine the causes of the congregation’s challenges in grasping the mission month topic at GKII Ungaran. For this qualitative study, the authors interviewed 22 youths at GKII Ungaran. Based on the study’s preliminary findings, which showed that the designated youth age group had trouble understanding the mission month sermon, informants from this age range were chosen as the main data source. This study reveals that communication challenges among members of the GKII Ungaran congregation are mostly due to cultural issues. This situation causes the respondent to receive an abstract explanation. Secondly, the language barrier made it challenging for the young to focus on understanding the sermon due to the preacher’s language use, the youths’ misconceptions, and their overt high regard for the sermon’s theme. Thirdly, the personal factors of the listeners—bad health, a lack of concentration, and exhaustion are some factors. Lastly, the sermons are difficult to comprehend due to communication-impairing instrument features such as sound systems.